Principles of trial in Shariah: an analysis in the modern context - Haneef, Sayed Sikandar Shah; Abdul Razak, Mohd Abbas; Laluddin, Hayatullah (LexiNexes, 2019)
Serious comparative scholars frown upon the predominant trends of judging non-Western modes of trial against Western system of trial. In consequence, there has been an awakening among the legal researchers to assert the essential features of trial for instance, in Pre-colonial Japanese culture and China. In the case of comparative analysis between Shariah system of adjudication with that of the Civil Law of France and Common Law of Anglo-American trial system, by and large, the approaches have been more of looking for commonality rather than highlighting dissimilarities. This may augur well for modernizing Shariah court procedures but burrs some of the essential features of Shariah adjudication with the risk of perverting the religious features of Shariah system which outsiders describe as the Westernization of the sharath conception of trial. This article aims at preempting this risk and argues that in the pursuit of modernizing Shariah system of adjudication, the organic relations between its ethico-legal and religious aspects should not be downplayed